Identity Formation Across Jane Smiley’s The Last Hundred Years Trilogy: A Century of Evolving Selfhood (MSW Management Journal, 2026)
This study investigates the evolution of identity across Jane Smiley’s The Last Hundred Years Trilogy, a work that chronicles five generations of the Langdon family from 1920 to 2019. Through a century of American transformation economic expansion, wars, technological acceleration, neoliberal reform, and global interconnectedness the trilogy frames identity as an evolving construct shaped by historical contingencies. The research examines how Smiley’s narrative reflects shifting modes of selfhood, tracing the movement from agrarian-rooted identities in Some Luck to ideologically conflicted mid-century subjectivities in Early Warning, and ultimately to fragmented, technologically mediated identities in Golden Age. Drawing upon Social Identity Theory, Marxist criticism, and socio-cultural perspectives on generational transmission, the article argues that identity in the trilogy emerges at the intersection of social roles, economic structures, and cultural practices. The findings reveal that personal identity is inseparable from collective experience and that each generation internalizes its historical moment as part of its psychological and social self-concept. This study contributes to contemporary literary analysis by demonstrating how long-form, multi-generational fiction can illuminate the cultural and emotional consequences of modernity and how identity evolves alongside structural transformation across time.